Deskripsi Pelaksanaan Model PBL dikaji dari Bernalar Kritis Siswa dalam Pembelajaran IPAS di Kelas IV SDN 03 Pontianak Selatan - Nabila Rusvayana; Bistari Bistari; Rio Pranata (Departement of Mathematics Education, 2024)
This research aims to describe the implementation of the PBL model studied from students' critical reasoning in science learning in class IV SDN 03 South Pontianak, the planning of the PBL model studied from students' critical reasoning, the implementation of the PBL model studied from students' critical reasoning and the obstacles faced by teachers in implementing the PBL model studied from students' critical reasoning in science learning. Using qualitative research with descriptive methods. Data sources are observation, interviews and documentation. Data collection techniques are observation and interviews. Research results in planning the PBL model must be prepared effectively, otherwise learning in the classroom will not run well resulting in students not being interested and focused. The implementation of science and science learning which consists of preliminary, core and closing activities, critical reasoning activities have been carried out quite well, the obstacles faced by teachers are adjusting teaching media to the material, ineffective implementation time, less conducive classroom conditions, students who are still unstable and busy themselves, not all materials can use PBL, they have to adapt to the material, students find it difficult to express opinions and are not confident.